Evaluate the Effectiveness of Training with Michael Frey Approach along with Drug Control in Reducing Anxiety, Increasing Adaptability and Resiliency Female High School students - Mohsen Saeidmanesh Saeidmanesh (Journal of Global Pharma Technology, 2017)
The aim of this study was to evaluate the effectiveness of training with Michael Frey approach along with drug control in reducing anxiety, increasing adaptability and resiliency is female high school students. The research method was experimental with pretest-posttest control group. The study population included all high school female students in Isfahan city were in the third quarter of 1395. Using 40 high school girls were selected by convenience sampling. Connor-Davidson Resilience and questionnaires, social adjustment Bell and Beck Anxiety Inventory was ¬Ml them and then randomly divided into two experimental and control groups. The experimental group in 12 sessions 90 sessions of cognitive behavioral group under Michael Frey was placed. Again, both Connor and Davidson Resiliency Questionnaire, social adjustment Bell and Beck Anxiety Inventory was taken. The results of analysis of covariance showed that cognitive-behavioral intervention anxiety level students Michael Frey significantly (P <0.05) decreased and the adaptability and resilience was seen significant changes. The results of this research can be concluded that cognitive-behavioral intervention to reduce anxiety Michael Frey students has a positive effect but had no significant effect on the resiliency and adaptability.Keywords: Training, Michael Frey, Anxiety, Resilience, Adaptability.